Novel lipophosphonoxin-loaded polycaprolactone electrospun nanofiber dressing reduces Staphylococcus aureus induced wound infection in mice - Do Pham, Duy Dinh; Jenčová, Věra; Kaňuchová, Miriam; Bayram, Jan; Grossová, Ivana; Šuca, Hubert; Urban, Lukáš; Havlíčková, Kristýna; Novotný, Vít; Mikeš, Petr; Mojr, Viktor; Asatiani, Nikifor; et al. (Scientific reports, 2021)
Active wound dressings are attracting extensive attention in soft tissue repair and regeneration, including bacteria-infected skin wound healing. As the wide use of antibiotics leads to drug resistance we present here a new concept of wound dressings based on the polycaprolactone nanofiber scaffold (NANO) releasing second generation lipophosphonoxin (LPPO) as antibacterial agent. Firstly, we demonstrated in vitro that LPPO released from NANO exerted antibacterial activity while not impairing proliferation/differentiation of fibroblasts and keratinocytes. Secondly, using a mouse model we showed that NANO loaded with LPPO significantly reduced the Staphylococcus aureus counts in infected wounds as evaluated 7 days post-surgery. Furthermore, the rate of degradation and subsequent LPPO release in infected wounds was also facilitated by lytic enzymes secreted by inoculated bacteria. Finally, LPPO displayed negligible to no systemic absorption. In conclusion, the composite antibacterial NANO-LPPO-based dressing reduces the bacterial load and promotes skin repair, with the potential to treat wounds in clinical settings.
Keywords: obvazy; Staphylococcal Infections; Animals; Wound Healing; Mice; hojení ran; Staphylococcus aureus; modely nemocí na zvířatech; Nanofibers; stafylokokové infekce; Anti-Bacterial Agents; nanovlákna; zvířata; Bandages; infekce v ráně; Wound Infection; antibakteriální látky; Disease Models, Animal; myši